1994
DOI: 10.1089/hum.1994.5.12-1477
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Following Direct Injection of DNA into Liver

Abstract: The liver is an attractive target tissue for gene therapy. Current approaches for hepatic gene delivery include retroviral and adenoviral vectors, liposome/DNA, and peptide/DNA complexes. This study describes a technique for direct injection of DNA into liver that led to significant gene expression. Gene expression was characterized in both rats and cats following injection of plasmid DNA encoding several different proteins. Luciferase activity was measured after injection of plasmid DNA encoding the luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(141 citation statements)
references
References 30 publications
2
136
0
3
Order By: Relevance
“…Following this initial discovery, many studies have reported success in expressing exogenous genes using local regional administration. [18][19][20][21][22][23] In this report, we have demonstrated that an efficient gene transfer and high level of transgene expression can also be achieved by systemic administration of plasmid DNA in animals by a rapid injection of DNA in large volume (Figures 1 and 2). Up to 300 ng of transgene product per milligram of extracted protein was obtained from the liver of a mouse after a single injection of as little as 5 g of plasmid DNA (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this initial discovery, many studies have reported success in expressing exogenous genes using local regional administration. [18][19][20][21][22][23] In this report, we have demonstrated that an efficient gene transfer and high level of transgene expression can also be achieved by systemic administration of plasmid DNA in animals by a rapid injection of DNA in large volume (Figures 1 and 2). Up to 300 ng of transgene product per milligram of extracted protein was obtained from the liver of a mouse after a single injection of as little as 5 g of plasmid DNA (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Compared with virus-mediated gene transfer systems, introduction of an exogenous gene into cells in the form of naked DNA has many obvious advantages. Preparation of DNA has become routine in many laboratories, and it is easy to obtain significant amounts of DNA without involving laborious procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The livers were collected and immediately frozen on dry ice. Approximately 200 mg of liver sample were used for DNA extraction.…”
Section: Southern Analysismentioning
confidence: 99%
“…2 Naked pDNA transfection was also successful into other organs, such as heart, 3 lung, 4 skin, 5 and liver. 6 More recently, very high transgene expression was achieved in the liver by intravascular delivery of pDNA. Budker et al 7 and Zhang et al 8 administered pDNA into the liver via the portal vein, hepatic vein or the bile duct.…”
mentioning
confidence: 99%